Phylogenetics of Serjania (Sapindaceae-Paullinieae), with emphasis on fruit evolution and the description of a new species from Michoacán, Mexico. Issue 1 (31st December 2022) - Steinmann, Victor W.; Ferrucci, MaríA S.; Maya-Lastra, Carlos A.
Abstract : Serjania is among the largest Neotropical genera of Sapindaceae and comprises ∼240 species. Traditionally, the genus has been defined by its schizocarpic fruits separating into three distally winged mericarps. However, recent phylogenetic studies have revealed that fruit type is not consistent within the genus and that it also includes a few species having capsular fruits that were previously placed in other genera. A phylogenetic analysis is presented based on nuclear ITS and chloroplast trn L-F sequences. The ingroup consisted of 48 species broadly sampled from across the geographic range and taxonomic spectrum of Serjania and focusing on species with atypical fruits. An ancestral character state reconstruction of fruit type was performed and demonstrated that the ancestral fruit type of the genus is strongly supported to be a schizocarp, but there are at least five independent derivations to capsular fruits and at least one transition back from capsules to schizocarps. Also, transitions from winged to wingless mericarps have occurred at least twice. Infrageneric classification is problematic and all of the sections that were represented by more than one species come out as poly- or paraphyletic. Our limited sample of taxa precludes the possibility of a new classification at present and a broader phylogenetic sample of the genus will be needed to understand relationships and determine which lineages warrant formal recognition. In addition to the phylogenetic study, Serjania frutescens, a new capsular-fruited species from Michoacán, Mexico, is described, illustrated, and compared with its putative closest relatives. A key is provided to differentiate this species from other Mexican Serjania with capsular fruits, and new synonymies and lectotypifications associated with capsular-fruited Serjania tortuosa and S. sonorensis are established. Phylogenetic results suggest that these two are cryptic species and at least superficially indistinguishable by morphology.